Quality of work life, anchor virtues, and work engagement: The moderating role of workload - Apsari, Dhiatira Biananda; Riyono, Bagus (HUMANITAS published by Universitas Ahmad Dahlan., 2025)
Work engagement is a critical issue across organizations due to its vital role in enhancing workplace well-being. This study examines the impact of quality of work life and anchor virtues on work engagement, with workload as a moderating variable, among Civil Servants (PNS) at the National Land Agency (BPN) in District X. A total of 101 active Civil Servants participated in this quantitative study. Data were collected using the Utrecht Work Engagement Scale (UWES), the Quality of Work Life Scale, the Anchor Personality Inventory (focusing on anchor virtues), and the Subjective Workload Assessment Technique (SWAT) Scale. Structural Equation Modeling (SEM) was conducted using Smart PLS version 3.0 to evaluate measurement models, test hypotheses, and analyze structural relationships. The findings reveal that workload moderates the relationships between quality of work life, anchor virtues, and work engagement. Specifically, the relationship between quality of work life and work engagement strengthens under high workload conditions. Conversely, the effect of anchor virtues on work engagement weakens as workload increases. These results highlight the complex dynamics of workload as a moderator and underscore the importance of quality of work life and anchor virtues in fostering work engagement among Civil Servants dedicated to public service